Hubungan Dukungan Keluarga dengan Kepatuhan Konsumsi Obat Infeksi Saluran Pernapasan Akut (ISPA) Masyarakat Pulau Pongok - Sinulingga, Syamsul Rizal (Politeknik Kesehatan Tanjungkarang, 2017)
Acute Respiratory Infection (ISPA) is the diseases of acute respiratory top dan bottom breather that caused by infection of bacteria, virus even the rickettsia with or without parenkim bronchiolus injury. This diseases common strike to adult and child. At 2012 according to the report from all primary healthcare facility around of Kabupaten Bangka Selatan that found and caring of the pneumonia inn child the highest score at in Puskesmas Pongok (27,5%) meanwhile lower at the Puskesmas Rias around (3,5%) and Puskesmas Airgegas around (1,9%). This research used by descriptive quantitative with a cross sectional approach and with bivariate statistic chi-square. According to the result of research that found common of the patient, ISPA is Child baby (58,3%) and child (18,8%). Variable of obedience that shows the highest score (95.8%). Variable of family support that results of score around 97,9%. The result of chi-square test that shows value p=0,00 that mean Ho reject and meaning have a significant relationship between family support with ISPA medication adherence. Commonly of ISPA patient is toddler and child, and from chi-square test that shown have a relationship between family support with ISPA medication adherence.